Economic benefits from the introduction of digital technologies in production processes ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses the economic benefits that enterprises can receive when introducing digital technologies into production processes. Key aspects such as increasing efficiency, reducing costs, improving product quality, and speeding up decision-making processes are highlighted in detail. The article examines examples of successful applications of digitalization at different stages of the production cycle and demonstrates how modern technologies such as the Internet of Things, artificial intelligence and automation contribute to the creation of more flexible and adaptive production systems.
Keywords: digital technologies; production processes; economic benefits; efficiency; automation; artificial intelligence